2015
DOI: 10.1007/s00256-015-2264-8
|View full text |Cite
|
Sign up to set email alerts
|

No association between pseudotumors, high serum metal-ion levels and metal hypersensitivity in large-head metal-on-metal total hip arthroplasty at 5–7-year follow-up

Abstract: We found no association between pseudotumor formation, serum metal-ion levels, metal patch test reactivity, and atopic dermatitis. However, clinicians should be aware of asymptomatic pseudotumors, and we advise further exploration into the mechanisms involved in the pathogenesis of pseudotumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 50 publications
0
27
0
2
Order By: Relevance
“…The results showed that when tissues of patients with suspected high wear were compared with those of patients with suspected metal sensitivity, the former had a lower ALVAL score and fewer lymphocytes but more macrophages and metal particles. Athanasou [78] postulated that while an increase in wear increases the frequency of ALVAL and pseudotumours in periprosthetic tissues, some reactions can be associated with low wear, likely owing to variability in the adaptive immune responses, and cited studies supporting this conclusion [181,182].…”
Section: Pathophysiology Of Metal Hypersensitivity Reactionsmentioning
confidence: 72%
“…The results showed that when tissues of patients with suspected high wear were compared with those of patients with suspected metal sensitivity, the former had a lower ALVAL score and fewer lymphocytes but more macrophages and metal particles. Athanasou [78] postulated that while an increase in wear increases the frequency of ALVAL and pseudotumours in periprosthetic tissues, some reactions can be associated with low wear, likely owing to variability in the adaptive immune responses, and cited studies supporting this conclusion [181,182].…”
Section: Pathophysiology Of Metal Hypersensitivity Reactionsmentioning
confidence: 72%
“…There is no significant association of metal allergy to pseudotumors, but the result of that study was based on a small group of cases 20 . Patients age seems to be another factor.…”
Section: Risk Factorsmentioning
confidence: 91%
“…Так, M.H. Hjorth et al отмечают развитие осложнений в 19,5% случаев [8], тогда как S. Konan et al регистрируют 32% осложнений [9]. Локальные осложнения пары трения металл-металл проявляются в виде грануляционных разрастаний в ответ на металлические частицы [10][11][12].…”
Section: локальные осложненияunclassified
“…Эти частицы (прежде всего, кобальта и хрома) образуются в результате износа пары трения, а также микроподвижности между головкой и конусом бедренного компонента эндопротеза. Эти частицы оказывают токсическое воздействие на мягкие ткани в области эндопротеза, вызывая атрофию мышц, а также развитие асептического некроза всех тканей (в том числе и костной) в области эндопротеза, с образованием полостей большого диаметра либо плотных масс [8].…”
Section: локальные осложненияunclassified